Implementação de um Tableau de Bord no Departamento de Financiamentos: Um Estudo no Setor de Retalho Automóvel - Manuel Conceição; Rosa Nunes; Trigo, A. (XXIII Congreso Internacional AECA, 2025)
This article applies the Design Science Research (DSR) methodology to develop andevaluate a Tableau de Bord implemented in the Financing Department of a company in thePortuguese automotive retail sector. The TDB replaced paper-based reports with a digital system based on strategic indicators. The results show improvements in efficiency, strategicalignment, and organizational acceptance. The study contributes to theory by illustrating thepractical applicability of DSR in the construction of management artefacts in competitivebusiness environments